In-house validation of a method for determining aflatoxins B1, B2, G1 and G2 in wheat and wheat by-products - Trombete,Felipe Machado (2014)
Aflatoxins are naturally occurring carcinogenic substances, extremely toxic to humans, which have been identified in wheat and wheat by-products. The use of reliable analytical methods to evaluate and monitor such contaminants is extremely important. This study aimed to in-house validate a methodology to determine aflatoxins B1, B2, G1 and G2 in wheat grains using pre-column derivatization and quantification by High Performance Liquid Chromatography with fluorescence detection (HPLC-FLD). Three methods were evaluated and the most suitable one was the method based on the extraction with chloroform, removal of interfering chemicals by filtration, liquid-liquid partition with hexane-methanol-water and methanol-water-chloroform and pre-column derivatization with trifluoroacetic acid. The method showed a Relative Standard Deviation lower than 15% and recovery values in the 70-110% range, with limits of detection and quantification (0.6 µg kg-1 and 1.2 µg kg-1, respectively) below the maximum level of aflatoxins allowed in wheat and wheat by-products by the European Commission (4.0 µg kg-1) and by the Brazilian legislation (5.0 µg kg-1). Using the validated method, aflatoxins were quantified in 20 commercial samples of wheat grains, wheat bran, whole wheat flour and refined wheat flour intended for direct human consumption. Six samples (30%) were positive for aflatoxins and all samples presented levels below the maximum limit stipulated by the Brazilian legislation.